Удосконалення технології хлібобулочних виробів, збагачених харчовими волокнами - Назар, Мар'яна Ігорівна (My University, 2018)
Дисертацію присвячено науковому обґрунтуванню та удосконаленню технології хлібобулочних виробів, збагачених харчовими волокнами. Науково обґрунтовано доцільність використання харчових волокон гороху (ХВГ) і харчових волокон картоплі (ХВК) для збагачення хлібобулочних виробів і впровадження їх у виробництво на міні-підприємствах при закладах ресторанного господарства. Визначено хімічний склад і технологічні властивості ХВГ та ХВК, їх вплив на технологічний процес, якість тіста та готових хлібобулочних виробів. Встановлено оптимальні параметри виробництва хліба з використанням ХВГ і ХВК для забезпечення належних споживчих властивостей готових виробів. Встановлено, що загальний вміст харчових волокон у ХВГ становить 61,6 %, у ХВК – 77,1 % до маси сухих речовин, що у 2,3...2,9 рази перевищує вміст харчових волокон у пшеничних висівках. Це, в свою чергу, дає змогу зменшити відсоток дозування досліджуваної сировини порівняно з пшеничними висівками для забезпечення фізіологічно виправданої концентрації ХВ у хлібобулочних виробах. Встановлено оптимальне дозування ХВГ і ХВК, запропоновано технологічні параметри, що забезпечують найкращі показники якості хліба. Доведено, що за умови додання в тісто ХВГ і ХВК покращуються споживчі властивості хлібобулочних виробів. Ступінь забезпечення добової потреби організму людини харчовими волокнами за умови споживання добової кількості пшеничного хліба з досліджуваною сировиною становить 35,0…56,6 %, житньо-пшеничного хліба – 50…68,4 %. В результаті проведених теоретичних та експериментальних досліджень розроблено і затверджено нормативну документацію на нові види хлібобулочних виробів, збагачених ХВГ і ХВК: батон «Весняний», хліб «Міський» із пшеничного борошна та хліб «Сонячний» і хліб «Літній» із суміші житнього і пшеничного борошна. The dissertation is devoted to scientific substantiation and improvement of technology of bakery products enriched with food fibers. It is scientifically substantiated the expediency of using peanut food fibers (PFF) and potato food fiber (PFF) for the enrichment of bakery products and introducing them into production at mini-enterprises of the restaurant industry. The chemical composition and technological properties of peanut food fibers and potato food fiber, their influence on the technological process, the quality of the dough and the finished bakery products are determined. The optimal parameters of bread production using peanut food fibers and potato food fiber have been established to provide the proper consumer properties of ready products. The influence of the new raw material on the biochemical and microbiological processes in the dough as well as their influence on the structural and mechanical properties of the dough and bread are determined, the consumer value and physiological efficiency of the use of new sources of PF s are substantiated. It was established that the total content of food fibers in peanut food fibers is 61,6%, in potato food fiber – 77,1% to the mass of dry matter, which is 2,3 ... 2,9 times higher than the content of food fibers in wheat bran. This makes it possible to reduce the percentage of dosing of the investigated raw material in comparison with wheat bran to ensure physiologically justified concentration of PF in bakery products. Peanuts and potato food fibers contain 20,3% and 18,9%, respectively, of SR pulp and 31,1% and 54,6%, respectively, of SR pectin substances represented predominantly by protopectin, which allows predicting the potential detoxification effect of bread with this raw material. The content of pectin substances in the investigated raw material exceeds their content in wheat bran in the range of 14,8 ... 26,0 times, which indicates the superiority of the peanut food fibers and the potato food fiber in terms of the medical and biological aspects of evaluating the use of different sources of food fibers. The introduction of peanut food fibers positively affects the activity of yeast, which contributes to the intensification of the process of fermentation and the formation of gas in the dough. This is the basis for reducing the total duration of cooking of wheat and rye-wheat dough with peanut food fibers. It has been established that peanut and potato food fiber has a high water absorption capacity, which contributes to the improvement of structural and mechanical properties with them. The use of peanut and potato dietary fiber reduces the caloric content of ready products and increases the shelf life. The optimal dosage of peanut food fibers and potato food fiber has been established, technological parameters have been proposed that provide the best indicators of bread quality.
Keywords: кафедра готельно-ресторанної справи; картопляна клітковина; харчові волокна; горохова клітковина; potato fiber; food fibers; pea fiber